INNOVATIVENESS AND COMPETITIVENESS IN CREATIVE INDUSTRIES: THE CASE OF SMES IN MAROS REGENCY - Narto Irawan Otoluwa; Ibriati Kartika Alimuddin; Nur Alamzah; Mursalim Nohong (Faculty of Economics and Business, Hasanuddin University, 2018)
The purpose of study was to explain the effect of entrepreneurship orientation and innovation in improving the performance and competitiveness of creative industries in Maros Regency. The primary data used in this study were collected by using questionnaires. The data is then processed in the form of descriptive statistics and inferential statistics. Based on the analysis, it is found that the orientation of entrepreneurship which is reflected by the activities of research and development activities, technological leadership, and innovation will be able to improve the performance and competitiveness of creative industry. Performance as measured by the company's ability to increase sales will be able to create competitiveness. The study also found an insignificant effect between innovation with competitiveness and performance with competitiveness